The role of Tetraspanins in digestive system tumor development: update and emerging evidence - Shao, Shijie; Bu, Zhen; Xiang, Jinghua; Liu, Jiachen; Tan, Rui; Sun, Han; Hu, Yuanwen; Wang, Yimin (Frontiers in Cell and Developmental Biology, 2024)
Digestive system malignancies, including cancers of the esophagus, pancreas, stomach, liver, and colorectum, are the leading causes of cancer-related deaths worldwide due to their high morbidity and poor prognosis. The lack of effective early diagnosis methods is a significant factor contributing to the poor prognosis for these malignancies.Tetraspanins (Tspans) are a superfamily of 4-transmembrane proteins (TM4SF), classified as low-molecular-weight glycoproteins, with 33 Tspan family members identified in humans to date. They interact with other membrane proteins or TM4SF members to form a functional platform on the cytoplasmic membrane called Tspanenriched microdomain (TEM) and serve multiple functions including cell adhesion, migration, propagation and signal transduction. In this review, we summarize the various roles of Tspans in the progression of digestive system tumors and the underlying molecular mechanisms in recent years. Generally, the expression of CD9, CD151, Tspan1, Tspan5, Tspan8, Tspan12, Tspan15, and Tspan31 are up-regulated, facilitating the migration and invasion of digestive system cancer cells. Conversely, Tspan7, CD82, CD63, Tspan7, and Tspan9 are down-regulated, suppressing digestive system tumor cell metastasis. Furthermore, the connection between Tspans and the metastasis of malignant bone tumors is reviewed. We also summarize the potential role of Tspans as novel immunotherapy targets and as an approach to overcome drug resistance. Finally, we discuss the potential clinical value and therapeutic targets of Tspans in the treatments of digestive system malignancies and provide some guidance for future research.